Inhibition of tumor growth, angiogenesis, and microcirculation by the novel Flk-1 inhibitor SU5416 as assessed by intravital multi-fluorescence videomicroscopy - Vajkoczy, Peter; Menger, Michael D.; Vollmar, Brigitte; Schilling, Lothar; Schmiedek, Peter; Hirth, K. Peter; Ullrich, Axel; Fong, T. Annie T. (Neoplasia, 1999)
Vascular endothelial growth factor (VEGF) plays a fundamental role in mediating tumor angiogenesis and tumor growth. Here we investigate the direct effect of a novel small molecule inhibitor of the Flk-1-mediated signal transduction pathway of VEGF, SU5416, on tumor angiogenesis and microhemodynamics of an experimental glioblastoma by using intravital multifluorescence videomicroscopy. SU5416 treatment significantly suppressed tumor growth. In parallel, SU5416 demonstrated a potent antiangiogenic activity, resulting in a significant reduction of both the total and functional vascular density of the tumor microvasculature, which indicates an impaired vascularization as well as significant perfusion failure in treated tumors. This malperfusion was not compensated for by changes in vessel diameter or recruitment of nonperfused vessels. Analyses of the tumor microcirculation revealed significant microhemodynamic changes after angiogenesis blockage such as a higher red blood cell velocity and blood flow in remnant tumor vessels when compared with controls. Our results demonstrate that the novel antiangiogenic concept of targeting the tyrosine kinase of Flk-1/KDR by means of a small molecule inhibitor represents an efficient strategy to control growth and progression of angiogenesis-dependent tumors. This study provides insight into microvascular consequences of Flk-1/KDR targeting in vivo and may have important implications for the future treatment of angiogenesis-dependent neoplasms.
Available online 5 April 2014
Gesehen am 24.03.2022